Enhanced Debugging with Traces. - PHILLIPS, PETER (Communications of the ACM, 2010)
The article discusses how debugging techniques used in the creation of emulators of computer programs can be utilized in computer programming. Emulators may be used to allow computers to run older programs such as video games. The author discusses how errors in register values due to a miscalculation can cause visual mistakes in programs and notes that emulators can be used to create trace files for central processing unit (CPU) operations that can locate errors in other emulators, including problems due to memory corruption and code errors.